Muscle glycome in idiopathic inflammatory myopathies - Campar, Ana (2023)
Funding: Supported by the Portugal 2020 Partnership Agreement’s Norte Portugal Regional Programme (NORTE 2020) (project NORTE-01-0145-FEDER-000029 ), Fundo Europeu de Desenvolvimento Regional (FEDER) funds from the Compete2020 Science, Technology, and Innovation Operational Programme (POCI), and the Portuguese Foundation for Science and Technology (FCT) (projects POCI-01/0145-FEDER-016601 and POCI-01-0145-FEDER-028772 ). A.C. work was supported by the Portuguese Society of Internal Medicine’s Group for Study of Autoimmune Diseases ( NEDAI ). I.A. and S.S.P. were also funded by Clinical Research in Autoimmunity prize (supported by National Medical Association in Autoimmunity (NEDAI) and National Society of Internal Medicine (SPMI)) and Pfizer prize (supported by Pfizer and Society of Medical Sciences of Lisbon ). Publisher Copyright: © 2023 The Author(s)